Penerapan Finger Painting dalam Melatih Kemampuan Motorik Halus Anak Usia 5-6 Tahun - Ayu Rubiana; Riskal Fitri; Ashar Ashar (Ihya Ulum: Early Childhood Education Journal, 2025)
This study aims to describe in depth the effectiveness and contribution of implementing finger painting activities in training and stimulating the fine motor skills of children aged 5–6 years. The main underlying problem of this study is the stiffness of finger muscles and weak hand-eye coordination in children during the preschool transition phase, which impacts their mechanical writing readiness. The research method employed is qualitative with a descriptive approach. Data collection was conducted through structured observation techniques, semi-structured interviews with the classroom teacher, and documentation of children's artwork portfolios. The research subjects involved 10 children from Group B at Tumbuh Kembang Kindergarten. The results indicated that tactile stimulation through finger painting significantly succeeded in transforming children's physical motor skills through seven planned pedagogical steps. Improvement in children's fine motor performance was consistently achieved across four main indicators, namely the ability to draw according to visual concepts, flexibility in executing intricate finger movements, maturity in hand-eye coordination synchronization, and tactile sensitivity in controlling the color paste medium. Aside from optimizing the strength of the digital hand muscles, this meaningful art activity also yielded collateral impacts in the form of enhanced creative imagination and the expansion of children's expressive language skills when narrating their artwork. This study concludes that finger painting is worthy of being systematically integrated into the early childhood education curriculum as a primary strategy for fine motor stimulation.